2022
DOI: 10.1093/plphys/kiac285
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic features drastically impact CRISPR–Cas9 efficacy in plants

Abstract: CRISPR–Cas9-mediated genome editing has been widely adopted for basic and applied biological research in eukaryotic systems. While many studies consider DNA sequences of CRISPR target sites as the primary determinant for CRISPR mutagenesis efficiency and mutation profiles, increasing evidence reveals the substantial role of chromatin context. Nonetheless, most prior studies are limited by the lack of sufficient epigenetic resources and/or by only transiently expressing CRISPR–Cas9 in a short time window. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…In the current issue of Plant Physiology , Weiss et al (2022) took an unbiased, genome-wide approach to identify sequence-independent factors that affect CRISPR–Cas9 efficacy and outcome in whole Arabidopsis ( Arabidopsis thaliana ) plants. To eliminate the effect that the gRNA sequence would have on Cas9 efficacy, the authors aimed to target identical short sequences within their specific, natural genomic context.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In the current issue of Plant Physiology , Weiss et al (2022) took an unbiased, genome-wide approach to identify sequence-independent factors that affect CRISPR–Cas9 efficacy and outcome in whole Arabidopsis ( Arabidopsis thaliana ) plants. To eliminate the effect that the gRNA sequence would have on Cas9 efficacy, the authors aimed to target identical short sequences within their specific, natural genomic context.…”
mentioning
confidence: 99%
“… Strategy for identifying chromatin features associated with CRISPR–Cas9 efficacy in plants. In the work presented by Weiss et al (2022) , a genome-wide search of the Arabidopsis genome identified over 7 million putative CRISPR target sites (20 nt followed by NGG, the PAM recognition site). Subsequently, Weiss et al filtered out sites with low number of repeats in the genome, with inappropriate GC content, and with target sequences in nonnuclear DNA.…”
mentioning
confidence: 99%
See 3 more Smart Citations